2023
DOI: 10.1186/s13068-023-02403-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genome-wide association study with transcriptomic data to predict candidate genes influencing Brassica napus root and biomass-related traits under low phosphorus conditions

Nazir Ahmad,
Sani Ibrahim,
Lieqiong Kuang
et al.

Abstract: Background Rapeseed (Brassica napus L.) is an essential source of edible oil and livestock feed, as well as a promising source of biofuel. Breeding crops with an ideal root system architecture (RSA) for high phosphorus use efficiency (PUE) is an effective way to reduce the use of phosphate fertilizers. However, the genetic mechanisms that underpin PUE in rapeseed remain elusive. To address this, we conducted a genome-wide association study (GWAS) in 327 rapeseed accessions to elucidate the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The recent GWAS conducted in Brassica napus had successfully pinpointed 12 genes linked to root growth and development under low phosphorus (LP) stress. Out of the identified set of twelve genes, six (BnaA04g23490D, BnaA09g08440D, BnaA09g04320D, BnaA09g04350D, BnaA09g04930D, BnaA09g09290D) showcased distinct patterns of expression, signifying their potential as prime candidate genes linked to the desired traits [41]. Similar studies regarding the GWAS on plant biomass were conducted in soybeans, deciphering in total 10 loci encompassing 47 putative candidate genes.…”
Section: Discussionmentioning
confidence: 81%
“…The recent GWAS conducted in Brassica napus had successfully pinpointed 12 genes linked to root growth and development under low phosphorus (LP) stress. Out of the identified set of twelve genes, six (BnaA04g23490D, BnaA09g08440D, BnaA09g04320D, BnaA09g04350D, BnaA09g04930D, BnaA09g09290D) showcased distinct patterns of expression, signifying their potential as prime candidate genes linked to the desired traits [41]. Similar studies regarding the GWAS on plant biomass were conducted in soybeans, deciphering in total 10 loci encompassing 47 putative candidate genes.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, homologs of three ABC transporter proteins implicated in root suberin synthesis exhibited co-localization with peaks associated with leaf nitrate and phosphorus levels. In another RSA study, Ahmad et al (2023) identified 39 significant single nucleotide polymorphisms (SNPs) on Brassica chromosomes A04, A09, A10, C02, C03, C07, and C09 that were associated with RSA and biomass traits in 327 rapeseed accessions under low phosphorus conditions. Fletcher et al (2016) also reported 20 QTLs on chromosomes A03, A10 and C02, associated with flowering time and root mass in a B. napus doubled haploid population, demonstrating their association with adaptation to drought.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, homologs of three ABC transporter proteins implicated in root suberin synthesis exhibited co-localization with peaks associated with leaf nitrate and phosphorus levels. In another RSA study, Ahmad et al. (2023) identified 39 significant single nucleotide polymorphisms (SNPs) on Brassica chromosomes A04, A09, A10, C02, C03, C07, and C09 that were associated with RSA and biomass traits in 327 rapeseed accessions under low phosphorus conditions.…”
Section: Introductionmentioning
confidence: 99%